The Generation and Characterization of Recombinant Protein and Antibodies of Clostridium perfringens Beta2 Toxin - Jin Zeng; Fuyang Song; Yi Yang; Chenjie Ma; Guangcun Deng; Yong Li; Yujiong Wang; Xiaoming Liu (Journal of Immunology Research)
Introduction. Clostridium perfringens (C. perfringens) beta2 toxin (CPB2) is an important virulent factor of necrotic enteritis in both animals and humans. However, studies of its pathogenic roles and functional mechanisms have been hampered due to the difficulty of purification and lack of specific antibodies against this toxin. Methods. A recombinant His-tagged C. perfringens beta2 (rCPB2) toxin and monoclonal antibodies (McAbs) against CPB2 were generated and characterized by assays of cytotoxicity, immunoblotting, ELISA, neutralization, and immunofluorescence. Results. A His-tagged rCPB2 with integrity and cytotoxicity of native CPB2 was purified from E. coli expressing system, which exhibited a moderate cytotoxicity on NCM460 human intestinal epithelial cells. The rCPB2 could induce apoptotic cell death rather than necrotic death in part through a pathway involved in caspase-3 signaling. Mechanistically, rCPB2 was able to first bind to cell membrane and dynamically translocate into cytoplasm for its cytotoxic activity. Three McAbs 1E23, 2G7 and 2H7 were characterized to be able to immunologically react with CPB2 and neutralize rCPB2 cytotoxicity on NCM460 cells. Conclusion. These results indicated the rCPB2 and antibodies generated in this study are useful tools for studies of biological functions and pathogenic mechanisms of CPB2 in future, which warrants for further investigations.